2017
DOI: 10.1002/mop.30389
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient microwave heating for target area based on metamaterial

Abstract: We describes a new setup based on metamaterial to enhance microwave heating efficiency for target area. Compared with conventional microwave heating, temperature rise of water can be increased 28% in this setup. Both experiments and simulations demonstrate microwave energy can be concentrated on target area to improve microwave heating efficiency. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:758–761, 2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…where λ 0 is the free space wavelength of the microwave; ε r is the relative dielectric constant; tan δ is the loss angle constant; and c = 3 × 10 8 m/s. The heating depth is given by Equations (5) and (6):…”
Section: Microwave Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…where λ 0 is the free space wavelength of the microwave; ε r is the relative dielectric constant; tan δ is the loss angle constant; and c = 3 × 10 8 m/s. The heating depth is given by Equations (5) and (6):…”
Section: Microwave Frequencymentioning
confidence: 99%
“…Considering the deficiencies of traditional deicing methods, in the field of de-icing agents, people began to consider how to reduce harm to the environment and the main project, tending to adopt environmentally-friendly snow-removing agents [5]; in terms of snow-melting ice technology, researchers focused on the suppression of frozen pavements, thermal heating, energy conversion, and other new technologies for melting snow [6,7]. Among them, the road deicing technology using microwave heating for de-icing has been widely popularized and applied.…”
Section: Introductionmentioning
confidence: 99%
“…In general, different microwave absorbing abilities of concrete and ice layer are the key points for the microwave deicing method. 19…”
Section: Principles Of the Microwave Deicing Methodsmentioning
confidence: 99%
“…Yazdi et al designed a periodic array of meta-surfaces that exhibited perfect asymmetric light absorption from one side . Wu et al used a double-layer meta-surface with several microwave energies, thus improving the heating efficiency of the target area . Our past research has shown that a meta-surface featuring a periodic groove structure can enable microwave asymmetric propagation within a rectangle waveguide and effectively heat continuous fluids with varying dielectric constants .…”
Section: Introductionmentioning
confidence: 99%
“…24 Wu et al used a double-layer meta-surface with several microwave energies, thus improving the heating efficiency of the target area. 25 Our past research has shown that a meta-surface featuring a periodic groove structure can enable microwave asymmetric propagation within a rectangle waveguide and effectively heat continuous fluids with varying dielectric constants. 26 However, the high electric field intensity within the meta-surface grooves poses a risk of discharge breakdown under high power.…”
Section: Introductionmentioning
confidence: 99%